TERAPI MUSIK RELAKSASI MENINGKATKAN KUALITAS TIDUR PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA JARA MARA PATI SINGARAJA - Ni Putu Emy Darma Yanti; Ni Made Aries Minarti; Ni Gusti Ayu Putu Triyani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Elderly is the age most vulnerable to disease. Most elderly people have psychological disturbances due to the tension because it is not able to adapt to the changes experienced. One of the impacts caused by stress or emotional tension is sleep disturbance. To solve the emotional stress is needed relax condition that can make elderly to sleep. This study aims to determine the effect of relaxation music therapy on sleep quality in elderly. The method used in this study was pre-experimental design with one-group pretest-posttest design. The sample amounted to 30 people who got through purposive sampling technique. Data collected through interviews using The SMH (St. Marry’s Hospital Sleep Quetionnaire). Results obtained before action 40% elderly have less quality of sleep, no elderly who have a good sleep quality. After the action 50% elderly have good sleep quality and no longer has the quality of sleep or less. Relaxation music therapy gives the effect of improvement on sleep quality in elderly. The statistical test used the Wilcoxon Sign Rank test (p ? 0.05). After analyzing the data, the results obtained, there was an effect of relaxation music therapy on sleep quality in elderly. Based on these results, it is suggested to the nurses to use these relaxation music therapy as an alternative therapy in treating sleep problems in elderly. Keywords: Elderly, Relaxation Music Therapy, Sleep Quality of Elderly